2020
DOI: 10.1371/journal.pone.0233953
|View full text |Cite
|
Sign up to set email alerts
|

Secretive and close? How sharing secrets may impact perceptions of distance

Abstract: Having secrets is incredibly common. However, secrecy has only recently started to receive more attention in research. What has largely been neglected so far are the consequences of secret-sharing for the relationship between sharer and receiver. In this project, we aim to fill this gap. Previous research has shown that closeness can make secret-sharing more likely. Building on research from the self-disclosure and relationship literature, we experimentally investigate whether secret-sharing might in turn incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…to close family and friends). This finding is in line with attachment principles as elevated attachment-related insecurities, particularly the Avoidance dimension, can result in a reluctance in self-disclosure, potentially owing to perceived negative views by others ( Slepian and Kirby, 2018 ; Jaffe and Douneva, 2020 ). This can include perceptions of defectiveness, shame, and rejection placing that individual at risk of emotional distance on matters of importance, particularly during stressful situations ( Mikulincer et al , 2003 ; Wei et al , 2005 ; Shaver and Mikulincer, 2007 ; Mikulincer and Shaver, 2016 ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…to close family and friends). This finding is in line with attachment principles as elevated attachment-related insecurities, particularly the Avoidance dimension, can result in a reluctance in self-disclosure, potentially owing to perceived negative views by others ( Slepian and Kirby, 2018 ; Jaffe and Douneva, 2020 ). This can include perceptions of defectiveness, shame, and rejection placing that individual at risk of emotional distance on matters of importance, particularly during stressful situations ( Mikulincer et al , 2003 ; Wei et al , 2005 ; Shaver and Mikulincer, 2007 ; Mikulincer and Shaver, 2016 ).…”
Section: Discussionsupporting
confidence: 81%
“…Inherently, maintaining and sharing secrets can influence how close someone feels towards another ( Jaffe and Douneva, 2020 ) with topic avoidance, that is non-disclosure about important information, potentially impinging upon psychological wellbeing and relationship satisfaction ( Caughlin and Afifi, 2004 ; Afifi and Caughlin, 2006 ). Both partner and social support are known to improve psychological adaptation and transition to parenthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This limitation reflects a recurring challenge in the study of secrets given that the very nature of a secret requires the target to be unaware of its existence (for an exception, see Caughlin et al, 2009, for a discussion of putative secrets). However, research has attempted to address this gap by having participants rate how their relationship with someone might change after being told a particular secret (Jaffé & Douneva, 2020). Another approach could be to recruit dyads and ask one partner about an ongoing secret and the other partner about the relationship more generally, or to conduct a longitudinal study that would allow for secrets to arise and be revealed over time.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, non-disclosure can be defined as the inclination of an individual to withhold personal information, encompassing thoughts, feelings, behaviors, and experiences, from others (Demir et al, 2020). Secrets, a ubiquitous aspect of human existence, entail the desire to keep personal information from being discovered by others (Jaffé and Douneva, 2020). Drawing parallels between the definitions of secrecy and non-disclosure, both involve the suppression of personal information, including problems, emotions, and experiences.…”
Section: Non-disclosure and Type Of Non-disclosurementioning
confidence: 99%